IMPLEMENTASI MODEL PEMBELAJARAN ROLE PLAYING DALAM MENINGKATKAN MINAT BELAJAR SISWA KELAS V PADA PELAJARAN AKIDAH AKHLAK - Farich Purwantoro; Nuntupa (UNZAH Genggong, 2021)
Student interest in class V MI Mazra'atul Ulum 01 Paciran Lamongan in some subjects is classified as low, one of the less desirable subjects is Akidah Akhlak, this is in accordance with the results of questionnaires and learning interest of 43 students, the percentage of high interest in learning and very high in the Akidah Akhlak subject, only 32.56%. One solution to overcome this problem is through the implementation of the Role Playing learning model. The purpose of this study was to determine the implementation of the role playing learning model in increasing student interest in learning class V Madrasah Ibtidaiyah Mazra'atul Ulum 01 Paciran Lamongan in akidah akhlak lessons. The research method used is Classroom Action Research (CAR) with the Kurt Lewin model approach, which each cycle consists of 4 main components. Data collection techniques used were tests of student understanding, attitude assessment, observation, interviews, and documentation. The results showed that the implementation of the Role Playing learning model from the results of student interest in learning was high and very high in the first cycle of 58.14% and increased in the second cycle to 76.74%. Student learning outcomes meet the pre-cycle KKM by 65.12%, then in cycle I it increases to 74.42%, then cycle II increases again to 83.72% and learning outcomes in cycle II are included in the very good category and have met the performance indicators determined. Keywords: Learning Interest, Role Playing Learning Model